Developing a competence framework for gerontological nursing in China: a two-phase research design including a needs analysis and verification study - Bea L. Dijkman; Marina Hirjaba; Wenwen Wang; Marjo Palovaara; Marjolein Annen; Merle Varik; Ying'ai Cui; Jing Li; Cornelia van Slochteren; Wang Jihong; Chen Feiteng; Yu Luo; et al. (BMC, 2022)
Abstract Background China faces a serious shortage of competent nurses who can address the healthcare needs of older people in an ageing society. Chinese higher education institutes face serious challenges when it comes to developing new curricula that are capable of educating sufficient numbers of competent gerontological nurses. Therefore, the aim of this research study was to identify and verify competencies for gerontological nurses in China that are needed to provide nursing care for the growing number of older people in all care settings. This study takes into account the possible opportunities that trends and developments may offer in the near future. Methods In this study, a two-phase research design was used. The first phase concerned needs analysis, including a situational analysis, a trend analysis and a competence analysis. This process resulted in a draft competence framework. The second phase addressed the verification of the competence framework through a two-round Delphi study with a panel of Chinese and European experts. This process led to the final competence framework. Results The final competence framework for gerontological nursing in China included six competencies divided into 13 essential and five relevant learning outcomes. The competencies are: 'providing gerontological care', 'communication and collaboration', 'organization of gerontological nursing care', 'health promotion', 'evidence-based nursing and lifelong learning' and 'professional behaviour'. Conclusion The framework comprehensively covers the six core competencies that nurses who care for older people should possess. These competencies are well-embedded in a Chinese context. The framework therefore offers concrete, practical suggestions for the competencies and skills that nursing graduates will need to work in current and future professions related to gerontological nursing education and practice.